PENGARUH MODEL PEMBELAJARAN BERBASIS STEAM (SCIENCE, TECHNOLOGY, ENGINEERING, ART, MATHEMATIC) TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA KELAS IV SD NEGERI RANCAKALONG - Rokayah; Asep Wawan Jatnika; Rangga Nugraha; Sutarman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to understand the impact of the STEAM learning model on the creative thinking skills of fourth-grade students at SDN Rancakalong in learning the concept of energy transformation. The research method uses a quantitative approach a one-group pretest-posttest design. The sample consists of 20 students divided based on gender. Data were collected through pretests and posttests, as well as assessments of learning product outcomes. The Liliefors normality test showed the data were normally distributed. The t-test showed a significant difference in students' creative thinking abilities before and after using the STEAM learning model. The STEAM learning model effectively enhances students' creativity in understanding the material concept. The implication of this research is that the use of STEAM can improve the quality of learning in elementary schools.